PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA TERHADAP HASIL BELAJAR PPKn SISWA SMA N 12 PEKANBARU - Wahyu Ramadhani; Sri Erlinda; Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of education in Indonesia must be improved, in accordance with the national education goals set out in the law. Students have substandard learning outcomes due to the learning process that takes place, which is mostly centered on the teacher as the main source. Interactive learning media is one of the choices in many media and learning resources, interactive learning media can help students understand the material with an attractive display. The purpose of this study was to determine the effect of using canva-based interactive learning media on Civics learning outcomes. Research methods are used to answer the formulation of problems and test the hypotheses that researchers do. In the research that the researchers conducted, the researchers used the Quasi Experimental Design method, namely seeing the results of the experimental class and control class whether there was a change. The research design form uses the Pretest-Posttest Control Group Design form. Data analysis was carried out using the calculation of the independent sample T-Test test obtained titung = 3.796 then determine df with the n-2 formula. The sample in this study was 72 so that df = 72-2 = 70. Based on df 70 at a significance level of 5%, ttable = 1.666 was obtained. This shows that the hypothesis in this study is accepted with tcount> ttable (Ha is accepted and H0 is rejected). So it can be concluded that there is an effect of interactive learning media on learning outcomes.